UPAYA PENINGKATAN KOMPETENSI GURU DALAM MODEL PEMBELAJARAN TEMATIK MELALUI WORKSHOP BAGI GURU KELAS 1, 2, DAN 3 DI MI NEGERI 1 BANYUMAS TAHUN 2019 - Saridin (Pusat Studi Pendidikan dan Kreativitas Guru, 2020)
This study aims to find out the improvement of the competence of grade 1, 2, and 3 teachers in the thematic learning model, find out what obstacles are faced by the teacher in applying thematic learning models, find out the responses of students in class to the application of thematic learning models, and know the effect of the workshop for teachers grade 1, 2, and 3. This type of research is the School Action Research (PTS). The subjects of this study were all teachers in grades 1, 2, and 3 of MI Negeri 1 Banyumas in the 2018/2019 Academic Year as many as 18 people. Data collection instruments used in this study were observation sheets, interview sheets, learning evaluation sheets for students, and teacher performance assessment rubric sheets. Data in this study were analyzed using descriptive statistics. The results of this study indicate that the workshop activities in increasing the competence of grade 1, 2, and 3 teachers in MI Negeri 1 Banyumas were successful and proven by student learning outcomes also increased to 70%.In addition, the teacher ’s response to this workshop was very good because it could share experiences and find solutions to learning problems together. The obstacle in this activity is the suggestion of infrastructure in the form of a thematic book that is lacking and often late in procurement.